Sources of New Life Insurance Product Ideas in LIC of India - Furquan Uddin, Furquan Uddin (International Research Journal of Business Studies, 2018)
The present complex nature of market has created sturdy challenges before the business world in the form of designing right product, right price, right placement and right promotion. In order to survive and thrive, a marketer has to focus on these challenges. Amongst, right product is most crucial which requires good and feasible ideas in all industries including life insurance. In fact, life insurance is perceived as an unsought and complicated financial product in India. The present paper is a humble attempt to examine the sources of new life insurance product ideas in LIC of India. The findings of the present study include the sources into six groups such as key stakeholders, workforce, organizational documents and other sources, research unit, competitors, and national and international source. It may be noticed the key stakeholders like Insurance Regulatory and Development Authority of India, actuary, top management, and policyholders play vital role in providing ideas in the new product development process of LIC of India.